Vzjaimosvjaz' fiziceskoj i techniceskoj podgotovlennosti zenscin v pryzke s sestom - Zacharcuk, D. G.; Miller, A. R.; Jagodin, V. M. (Teorija i Praktika fiziceskoj Kul'tury, 2007)
The analysis of the special literature and questionnaire of athletes, coaches and specialists in pole vaults, has revealed the contradictions between high requirements of sports-technical preparedness of athletes and the insufficient development of methodical supply of technical training of elite female athletes. the Growth of sports result in this kind of sports in many respects depends on what rational technique is and how effectively an athlete masters it.